The Anatomical Society's Core Anatomy Syllabus for Dental Undergraduates. Issue 4 (14th February 2020) - Matthan, J; Cobb, M; McHanwell, S; Moxham, B J; Finn, G M
Abstract: The Anatomical Society has developed a series of learning outcomes in consultation with dentists, dental educators and anatomists delivering anatomical content to undergraduate dental students. A modified Delphi methodology was adopted to select experts within the field that would recommend core anatomical content in undergraduate dental programmes throughout the UK. Utilising the extensive learning outcomes from two UK Dental Schools, and neuroanatomy learning outcomes that remained outside the Anatomical Society's Core Gross Anatomy Syllabus for Medical Students, a modified Delphi technique was utilised to develop dental anatomical learning outcomes relevant to dental graduates. The Delphi panel consisted of 62 individuals ( n  = 62) from a wide pool of educators associated with the majority of undergraduate dental schools in the UK, representing a broad spectrum of UK Higher Education Institutions. The output from this study was 147 anatomical learning outcomes deemed to be applicable to all dental undergraduate programmes in the UK. The new recommended core anatomy syllabus for dental undergraduates, grouped into body regions, offers a comprehensive anatomical framework with which to scaffold clinical practice. The syllabus, presented as a set of learning outcomes, may be used in a variety of pedagogic situations, including where anatomy teaching exists within an integrated dental curriculum (both horizontally in the basic sciences part of the curriculum and vertically within the clinical years). Abstract : The new recommended core anatomy syllabus for dental undergraduates offers a comprehensive anatomical framework with which to scaffold clinical practice. Presented as a set of 147 learning outcomes, the syllabus may be used in a variety of pedagogic situations, including where anatomy teaching exists within an integrated dental curriculum.